2020
DOI: 10.1093/jme/tjaa069
|View full text |Cite
|
Sign up to set email alerts
|

Biological Parameters of Two Triatoma rubida Subspecies (Hemiptera: Reduviidae) and Their Laboratory Hybrids

Abstract: Chagas disease is one of the most important vector-borne diseases in Latin America, including Mexico. Recently, autochthonous cases have also been detected in the United States of America. It is suspected that two subspecies of Triatoma rubida (Uhler), T. r. sonoriana (Usinger) and T. r. uhleri (Usinger), considered efficient vectors of Trypanosoma cruzi Chagas in Mexico, could interbreed and potentially generate offspring with superior biological characteristics. In this study, the biological parameters of T.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…In addition, Mexican triatomine F1 hybrids also resulted in F1 offspring that were morphologically indistinguishable from one of the parental lines [ 39 ] and in second-generation hybrids (F2) with phenotypic characteristics either specific to those of one of the parents or with intermediate characteristics [ 40 , 41 ]. Considering that some factors can result in an increased risk of T. cruzi transmission to humans and animals (such as vigor [ 42 ] and hybrid fitness [ 43 ]) and that recently it has been reported that hybrids of the T. phyllosoma subcomplex show greater potential to acquire and transmit T. cruzi than parental species [ 44 , 45 ], the study of segregation of external morphology can also be of epidemiological importance [ 37 , 38 ].
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…In addition, Mexican triatomine F1 hybrids also resulted in F1 offspring that were morphologically indistinguishable from one of the parental lines [ 39 ] and in second-generation hybrids (F2) with phenotypic characteristics either specific to those of one of the parents or with intermediate characteristics [ 40 , 41 ]. Considering that some factors can result in an increased risk of T. cruzi transmission to humans and animals (such as vigor [ 42 ] and hybrid fitness [ 43 ]) and that recently it has been reported that hybrids of the T. phyllosoma subcomplex show greater potential to acquire and transmit T. cruzi than parental species [ 44 , 45 ], the study of segregation of external morphology can also be of epidemiological importance [ 37 , 38 ].
Fig.
…”
Section: Resultsmentioning
confidence: 99%